Muhammad Ali Jinnah the Greatest Advocate of Women- on the condition of Women in Pakistan: An Empirical Analysis - Muqadas Afzal Khan; Dr. Muhammad Adil; Dr Muhammad Inamullah (Al Manhal Research Journal, 2024)
The present article explores concept of influence of Quaid-e-Azam Muhammad Ali Jinnah’s stance on women’s rights regarding women empowerment in Pakistan. Quaid vision of women empowerment elaborates the importance of women involvement in every field of life like education, political affairs and national development. The results of the study indicate a positive correlation of Quaid-e-Azam’s advocacy for women’s involvement and Pakistani women’s advancement. According to him, no nation can make progress in the true sense unless its women participate in the development process along with men. This article argues that Quaid’s vision of women empowerment emphasizes the importance of women role in national development and in Pakistan movement, spirit of sacrifice in women, women participation in political struggle, their equal rights and presentation of women as third power in the world.